HUḌŪRI (INNATE IDEA) SEBAGAI BASIS PENGETAHUAN: STUDI KRITIK ATAS TEORI TABULARASA JOHN LOCKE BERSADARKAN PRINSIP EPISTEMOLOGI ṬABAṬABA’Ī - Qotrun Nada Annuri (Sekolah Tinggi Agama Islam Sadra, 2021)
Empiricism is a philosophical school that focuses knowledge only on the senses. John Locke is part of the empiricist figures. In Locke's view, he emphasizes that knowledge comes from observations made around humans by means of what John Locke called sensing, which is to regard this as a white sheet of paper (tabula rasa) and reject innate ideas. Locke views reason as a passive shelter receiving the results of the senses. Locke considered what he called knowledge to be a composite of ideas derived from sensory experience. Locke generalizes to knowledge. This study aims to answer the problems that arise from Locke's view by criticizing the tabularasa theory based on ḥuḍūri science by using ḥuḍūri according to Ṭabāṭabā'ī. This study uses qualitative methods and literature. The process of analyzing the data uses a critical demonstration theory approach. The result of this research is that ḥuḍūri science is the capital for every knowledge even for knowledge that is preceded by the senses. In essence, knowledge is something immaterial, what enters the subject who knows is something immaterial too, even though the object is bound by matter. This is what is called the presence of something immaterial in the immaterial soul.